Former à la traduction multimodale - Léchauguette, Sophie (Studia Romanica Posnaniensia, 2021)
Many books designed for international distribution combine text blocks and images. Their layout offers hybrid messages organized on the visual space of a double page. Texts both in the original language and in translation must fit into limited spaces or boxes positioned around illustrations. Thus, translators practice multimodal translation, writing texts that preserve or enhance the cohesion between visual and textual messages. This skill requires some training. Unfortunately, while theoretical writings on pragmatic translation acknowledge its intersemiotic nature, few training programs address this aspect. The creation of a course on multimodal translation would be a valued addition to any translator training program. The concept of a hybrid translation unit offers a way of structuring material to introduce both intersemiotic and multimodal translation in professional curricula. The author draws on her professional experience to discuss the role of illustrations in grasping meaning through practical examples. She suggests generalizable translation strategies to strengthen text-image cohesion, or even generate text from images alone, while adapting the book in translation to its intended readership.